Characteristics of Donors Who Experienced Donor Rejection Due to High Blood Pressure At UDD PMI Kota Surabaya In January-October 2024 - Ni Luh Putu Eka Sudiwati; Kurnia Gema Atmaja; Ardi Panggayuh; Nia Lukita Ariani; Sasi Widuri (Care : Jurnal Ilmiah Ilmu Kesehatan, 2025)
Blood pressure is one of the parameters used as a reference for the success of donor selection. Blood pressure is the pressure pumped by the heart against the artery walls. Acceptance criteria in donor selection regarding blood pressure are a systolic pressure of prospective donors of 90-160 mmHg, with a diastolic pressure of 60-100 mmHg. This study aims to determine the characteristics of donors who experienced rejection due to high blood pressure. The research design used was descriptive quantitative. The population in this study was all donors who were rejected due to high blood pressure with a total sampling technique. Data were collected using a tally sheet. Data were obtained from secondary data documentation studies from the management information system application (Hero Blood) and analyzed using frequency distribution and percentage of the characteristics of rejection due to high blood pressure. The results showed that rejection of prospective donors due to high blood pressure was most common in the age group 46-55 years (38.49%), male donors (82.57%), blood type O (40.94%), and private employees (54.85%). These findings emphasize the importance of early detection of blood pressure, especially in male donor candidates aged over 46 years. For further research, it is important to detect factors that influence the incidence of hypertension in potential donors.